Sympathetic‐Parasympathetic Interaction and Externalizing Problems in Children with Autism Spectrum Disorder. Issue 12 (9th August 2019) - Fenning, Rachel M.; Erath, Stephen A.; Baker, Jason K.; Messinger, Daniel S.; Moffitt, Jacquelyn; Baucom, Brian R.; Kaeppler, Alexander K.
Abstract : Children with autism spectrum disorder (ASD) exhibit significant difficulties with emotion regulation and reactivity, which may be linked to underlying psychophysiology. The present study examined associations between autonomic nervous system activity and individual differences in externalizing behavior problems in children with ASD. A multisystem approach was adopted to consider the interplay between markers of sympathetic (electrodermal reactivity—EDA‐R) and parasympathetic reactivity (respiratory sinus arrhythmia reactivity—RSA‐R) in relation to behavioral challenges. Fifty‐two children with ASD ages 6–10 years contributed complete psychophysiological data. Measures of EDA‐R and RSA‐R (RSA withdrawal) were obtained in response to a laboratory challenge task and parents reported on child externalizing behavior problems using a standardized questionnaire and a structured clinical interview. An equifinality model was supported, with two distinct psychophysiological pathways linked to heightened externalizing behavior problems. Greater RSA‐R was associated with more externalizing problems in the context of higher levels of EDA‐R, and lower EDA‐R was associated with increased externalizing problems at lower levels of RSA‐R. Findings underscore the importance of considering the role of psychophysiology in the unfolding of comorbid externalizing problems in children with ASD. Potential implications for tailoring coregulatory supports are discussed. Autism Res 2019, 12: 1805–1816 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Children with autism spectrum disorder (ASD) exhibit elevated rates of challenging behavior. This study identified specific psychophysiological profiles (low sympathetic‐low parasympathetic reactivity, and high sympathetic‐high parasympathetic reactivity) that may place these children at greater risk for behavior problems. Findings have implications for better understanding behavioral challenges in children with ASD, and for tailoring supports to address underlying psychophysiology.